Channel impulse response insensitive feature for non-coherent signal detection in molecular communication - Limin XIAO; Xiangrong XU; Zhuangkun WEI; Shenghan LIU; Yiwen LIU (Tongxin xuebao)
To solve the inter-symbol interference (ISI) and background noise challenges of molecular communication via diffusion (MCvD),four ISI-resistant signal-features were deployed,and a reliable non-coherent signal detection algorithm,which was insensitive to different types of molecular channel impulse response (CIR),was proposed.Also,an adaptive decision threshold and theoretical bound of bit error rate (BER) were deduced.Simulation results demonstrate a lower BER of the proposed non-coherent scheme compared to the state-of-the-art schemes in the same order of computational complexity,therefore suggesting its potential applications for future nano-scale MC.